The Relevance of Solubility and Miscibility for the Performance of Organic Solar Cells - Langner, Stefan; Perea Ospina, Jose Dario; Zhang, Chaohong; Li, Ning; Brabec, Christoph (CRC Press, 2019)
This chapter introduces the approach to ab initio calculate the values based on computational methods, and a Figure of Merit to predict the microstructure stability of bulk heterojunction (BHJ) composites. It focuses on solute-liquid miscibility and solute-solute miscibility and explains the degradation mechanisms related to microstructure. The chapter provides a detailed insight into the theoretical, computational and experimental principles of mixing of organic semiconductors. The microstructure of a BHJ film is determined by the competition between thermodynamics and kinetics during the drying process. The chapter describes the M. L. Hansen solubility parameters (HSPs) can be visualized in a three dimensional coordinates system with the solubility parameters as axes. The mixing compatibility of a polymer and a fullerene is graphically represented by the values of thermodynamic variables when the equilibrium is established among the phases of a system.
CRIS-Team Scopus Importer:2023-03-07